2015
DOI: 10.3762/bjoc.11.176
|View full text |Cite
|
Sign up to set email alerts
|

Robust bifunctional aluminium–salen catalysts for the preparation of cyclic carbonates from carbon dioxide and epoxides

Abstract: SummaryTwo new one-component aluminium-based catalysts for the reaction between epoxides and carbon dioxide have been prepared. The catalysts are composed of aluminium–salen chloride complexes with trialkylammonium groups directly attached to the aromatic rings of the salen ligand. With terminal epoxides, the catalysts induced the formation of cyclic carbonates under mild reaction conditions (25–35 °C; 1–10 bar carbon dioxide pressure). However, with cyclohexene oxide under the same reaction conditions, the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 35 publications
1
31
0
Order By: Relevance
“…Many aluminum complexes containing salen‐based ligands used as catalysts for the coupling of CO 2 with epoxides have been reported in the literature . However, compared to the conditions developed in this study, previously reported reaction conditions for this transformation are much harsher.…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…Many aluminum complexes containing salen‐based ligands used as catalysts for the coupling of CO 2 with epoxides have been reported in the literature . However, compared to the conditions developed in this study, previously reported reaction conditions for this transformation are much harsher.…”
Section: Resultsmentioning
confidence: 90%
“…Generally, salen‐based aluminum complexes have poor solubility in common organic solvents , . Thus, many salen‐based aluminum catalysts for the coupling of CO 2 and epoxides have a tert ‐butyl group at the 3‐position of the phenolate ring to improve their solubility in epoxides, which are common solvents for this transformation . Until now, aluminum complexes containing a methyl group at the 3‐position of the phenolate ring of the salen ligands have never been reported as catalysts for the cycloaddition of CO 2 to epoxides.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations